Innovative Strategies to Increase Public Awareness of the Importance of Physical Fitness to Health: Systematic literature review - Putra, Raffiandy Alsyifa; Bafirman, Bafirman; Arsil, Arsil; Bahtra, Ridho; Rahman, Dally; Haris, Fahmil; Zarya, Fiky (Poltekkes Kemenkes Palu, 2024)
In this modern era, unhealthy living habits and lack of physical activity have led to increasing health problems related to physical fitness. Therefore, it is important to inspire people to be more aware of the importance of maintaining health and fitness. The purpose of this study discuss innovative strategies in increasing public awareness of the importance of physical fitness through the magic of motivation. This research uses a qualitative descriptive research model that is a literature study that uses various literature reviews to strengthen research analysis. This research began by collecting some literature, then conducted a review and the collected literature was analyzed with a critical Appraisal table of 10 literature. This study explores new and innovative motivational approaches to influence people to increase their awareness of physical fitness. Various motivational strategies, such as technology use, gamification, support communities, and promotion through social media, were analyzed in the context of increasing active participation in physical activity. The results of this study show that the implementation of innovative motivation strategies can have a significant effect in increasing public awareness of the importance of physical fitness. Technology can be used to track progress and provide motivation through apps and wearable devices. The use of game or gamification elements in fitness programs also helps increase community participation and engagement. The study concludes that innovative motivational strategies can work wonders in raising public awareness of the importance of physical fitness. With a creative and integrated approach, we can encourage behaviour change and help people to adopt healthier lifestyles, and maintain their health and fitness.